Assembly and crystallization of the complex between the human T cell coreceptor CD8alpha homodimer and HLA-A2. - Gao, G; Gerth, U; Wyer, JR; Willcox, B; O'Callaghan, C; Zhang, Z; Jones, E; Bell, J; Jakobsen, B (1998)
A strategy for overexpression in Escherichia coli of the extracellular immunoglobulin domain of human CD8alpha was devised using codon usage alterations in the 5' region of the gene, designed so as to prevent the formation of secondary structures in the mRNA. A fragment of CD8alpha, comprising residues 1-120 of the mature protein, excluding the signal peptide and the membrane-proximal stalk region, was recovered from bacterial inclusion bodies and refolded to produce a single species of homodimeric, soluble receptor. HLA-A2 heavy chain, beta2-microglobulin and a synthetic peptide antigen corresponding to the pol epitope from HIV-1 were also expressed in E. coli, refolded and purified. CD8alpha/HLA-A2 complexes were formed in solution and by co-crystallization with a stoichiometry of one CD8alpha alpha dimer to one HLA-A2-peptide unit.